Respuesta :

Answer:

[tex]x= \dfrac{bma}{bm+1}[/tex]

Explanation:

Given expression:

[tex]\hookrightarrow b = \dfrac{x}{m(a-x)}[/tex]

shift the variables

[tex]\hookrightarrow b m(a-x)= x[/tex]

distribute inside parenthesis

[tex]\hookrightarrow bma-bmx= x[/tex]

collect terms with "x" in one side

[tex]\hookrightarrow -bmx-x= -bma[/tex]

divide both sides by -1

[tex]\hookrightarrow bmx+x= bma[/tex]

factor out common term "x"

[tex]\hookrightarrow x(bm+1)= bma[/tex]

shift the variables making "x" the subject

[tex]\hookrightarrow x= \dfrac{bma}{bm+1}[/tex]